Performance time differentials in the sprint proloque of elite cross-country skiers - Spencer, M.; Hallén, J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Analyses of elite competitive performance provide useful information for research and practical applications. We have recently reported the variability and predictability of performance times for distance and sprint events of elite skiers (1). The purpose of this study was to provide a detailed analysis of the time differentials in the sprint prologue of elite cross-country skiers.